ANALISIS PERBEDAAN HARGA SAHAM, LIKUIDITAS, DAN PROFITABILITAS PADA PERUSAHAAN RETAIL ANTARA SEBELUM DENGAN MASA COVID-19 - Gemala, Nila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022, 2022)
The study was conducted with the aim of empirically testing the impact of covid-19 whether companies experienced differences in stock prices, liquidity ratios and profitability ratios between before and during the covid-19 period in retail companies. This research is a comparative study that compares two conditions, namely before the entry of covid-19 in Indonesia in 2019 with the time of covid-19 in 2020. The research population is retail companies listed on the IDX by sampling by purposive sampling. The results of the study show that there is no significant difference in stock prices and liquidity ratios of retail companies before and during the Covid-19 period. Meanwhile, in the profitability ratio, there is a significant difference before and during the time when COVID-19 entered Indonesia.